Diseño de un sistema hibrido para controlar el acceso a los estacionamientos utilizando tarjetas magnéticas y con tecnología bluetooth de teléfono celular e implementación de un prototipo en el parqueadero de la UNACH. - Mejía Quinteros, Darling Ramiro (2012)
In order to improve security, this project aims to provide a solution to control vehicle access to the facilities of the Universidad National de Chimborazo. For the identification of users has considered using RFID (radio frequency identification) and via existing Bluetooth technology in mobile phones allow access to the parking lot of the Universidad Nacional de Chimborazo people previously registered and authorized visitors, giving priority to teachers, administrators and students.